The Social and Economic Preconditions for Ensuring of National Security under Conditions of Globalization. (Economics and region, 2018)
The peculiarities of national security ensuring under the conditions of strengthening of the globalization processes in the world are investigated. It was defined, that national security ensuring is an even more urgent task of each state in the globalized world, by directing its efforts to protect and adhere to the national interests in the political, economic, scientific, technological, demographic, informational, social, military, environmental spheres. Although globalization has both positive and negative effects, the correlation analysis of globalization and peace indexes by the countries of the world has allowed to state the rather positive impact of globalization processes on the states’ national security. The comparative analysis of Ukraine’s rating positions by the values of the index of prosperity, the international index of energy security, etc. indicates a deterioration of the country’s position and the extremely low level of prosperity and security. The ways of improvement of the socio-economic prerequisites for ensuring national security in Ukraine under the conditions of globalization and acceleration of the states’ development on the innovative basis are substantiated. In this context, it was suggested such ways of improvement: increasing the share of state financing of R&D to 1.5%; establishing the strategic priorities of the country’s innovation development; forming and development of innovative-integrated structures (clusters, venture companies, scientific parks, etc.); development of territorial and sectoral innovation infrastructure; establishing the cooperation between public authorities and educational institutions and business structures on the basis of social partnership; integration of national and regional innovative systems to the globalized world economic space; improvement of the quality and practical orientation of vocational education; establishing the energy-efficient and saving technologies; stimulating the development of small and medium-sized businesses; using the tax incentive tools for business entities; facilitating the forming of powerful research centers on the basis of institutions of higher education; increasing the level of investment attractiveness of the state.
Keywords: national security; globalization; socio-economic preconditions; index of peace; index of globalization